1999
DOI: 10.1097/00007632-199910150-00003
|View full text |Cite
|
Sign up to set email alerts
|

Association of Atherosclerosis with Low Back Pain and the Degree of Disc Degeneration

Abstract: A significant association is indicated between atheromatous lesions in the abdominal aorta and low back pain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
59
0
5

Year Published

2006
2006
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 105 publications
(68 citation statements)
references
References 13 publications
4
59
0
5
Order By: Relevance
“…Typically, atherosclerotic lesions occur in the bifurcation region, where the orifices of the lumbar arteries are located [6]. Consistently, it has been suggested that atherosclerotic arterial occlusion in the supplying arteries leads progressive disc degeneration and back symptoms due to a decrease in the nutrition of the disc tissue [5,6,21].…”
Section: Discussionmentioning
confidence: 98%
See 4 more Smart Citations
“…Typically, atherosclerotic lesions occur in the bifurcation region, where the orifices of the lumbar arteries are located [6]. Consistently, it has been suggested that atherosclerotic arterial occlusion in the supplying arteries leads progressive disc degeneration and back symptoms due to a decrease in the nutrition of the disc tissue [5,6,21].…”
Section: Discussionmentioning
confidence: 98%
“…It is well-known that blood supply of the lumbar intervertebral disc, the largest avascular tissue in the human body, is provided by the branches of the abdominal aorta [5,6,21]. Typically, atherosclerotic lesions occur in the bifurcation region, where the orifices of the lumbar arteries are located [6].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations